Online Learning Contract: A Way Disciplining Students - Noviyanti, Sari Dewi (Journal of Language Intelligence and Culture, 2021)
The contract between teacher and student or what is often called as teacher-student agreement is one of the class management in applying student discipline. Good class management, especially in student discipline, is considered important in creating a conducive learning atmosphere. In conventional learning, teacher and student contracts regarding student discipline are related to how students' attitudes in participating in learning, such as students not being allowed to go around the class while learning is taking place, students are not allowed to be busy with other things besides those related to learning and others. At this time, when online learning or distance learning is applied, of course this contract is also undergoing changes. There is a disciplinary agreement between the teacher and students that adapts to distance learning conditions. This study aims to identify the learning discipline contract between students and teachers in distance learning. Questionnaires and interviews were used to collect data. The data were analysed descriptively to get a description of the agreement between teachers and students in online learning and the type of agreement that commonly used. The findings show that the most widely regulation is related to student’s obedience in following teacher’s instruction in online class. This study also revealed that learning contract is an effective way to create a successful online learning based on teacher’s perspectives.